The clinical significance of parathyroid tissue calcium sensing receptor gene polymorphisms and expression levels in end-stage renal disease patients - (:unkn) unknown (My University, 2009)
Background: The calcium sending receptor (CaSR) allows parathyroid and kidney tubular cells to regulate PTH secretion and tubular calcium reabsorption. In the present report, we examined the relationship between CaSR gene polymorphisms and parathyroid CaSR expression and serum calcium/parathyroid hormone (PTH) levels and clinical progress in ESRD patients in the Turkish population. Methods: We genotyped the CaSR R990G and Q1011E variants in 192 end-stage renal disease (ESRD) patients by allele-specific PCR. CaSR expression in parathyroid tissues of operated 33 patients was quantified with quantitative reverse transcription-PCR. Results: Compared with other genotypes, the ratio of both codon 990-AA and 1011-CC polymorphisms was found higher in operated patients (p = 0.001). In the total patient group PTH levels were found higher in patients with CC1011 genotype than those with CG1011 (1015.15 ± 925.41 pg/ml; 523.84 ± 544.6 pg/ml, respectively, p = 0.002). There were statistically important higher Ca2+ levels in the AA990 allele carrying cases than AG990 positive ones (9.3 ± 1.0 mg/dl vs. 8.8 ± 0.9, p = 0.006). On the other hand, the expression of CaSR in parathyroid tissue was found inversely proportional with serum PTH level (r = -0.71). Conclusion: Present data suggest that co-presence of CaSR geneAA990 and CC1011 alleles is a possible risk factor for bad prognosis in secondary hyperparathyroidism. Patients carrying this genotype have tendency to require operation early in their medical therapy period and need postoperative close follow up for possible recurrences. © 2009 Dustri-Verlag Dr. K. Feistle.
Keywords: CaSR; End-stage renal disease; Polymorphisms; PTH; Secondary hyperparathyroidism